Direct Torque Control for Three-Level Neutral Point Clamped Inverter-Fed Induction Motor Drive - Sahu, M. K.; Panda, A. K.; Panigrahi, B. P. (Engineering, Technology & Applied Science Research, 2012)
Direct torque control (DTC) is a control technique in AC drive systems to obtain high performance torque control. The classical DTC drive contains a pair of hysteresis comparators and suffers from variable switching frequency and high torque ripple. These problems can be solved by using space vector depending on the reference torque and flux. In this paper the space vector modulation technique is applied to the three-level Neutral Point Clamped (NPC) inverter control in the proposed DTC-based induction motor drive system, resulting to a significant reduce of torque ripple. Three-level neutral point clamped inverters have been widely used in medium voltage applications. This type of inverters have several advantages over standard two-level VSI, such as greater number of levels in the output voltage waveforms, less harmonic distortion in voltage and current waveforms and lower switching frequencies. This paper emphasizes the derivation of switching states using the Space Vector Pulse Width Modulation (SVPWM) technique. The control scheme is implemented using Matlab/Simulink. Experimental results using dSPACE validate the steady-state and the dynamic performance of the proposed control strategy.